Assessing the antenatal care-seeking determinants associated with the penetration of the WHO eight-visit antenatal care policy across states in Nigeria - Christiana Ikemeh; Adedayo O. Adeyemi; Kazeem Arogundade; Leah M. Frerichs; Christopher M. Shea; Justin G. Trogdon (BMC Pregnancy and Childbirth)
Abstract Background Following the adoption and implementation of the 2016 WHO eight-visit antenatal care (8vANC) policy in Nigeria, a national cross-sectional survey conducted in 2021 indicated significant state-level differences in the utilization rates of 8vANC. Methods We used a post-implementation sample, n = 9,416, obtained from the Nigeria Multiple Indicator Cluster Survey 2021 data to perform secondary analyses using the theory, model, and framework (TMF) implementation research approach. The outcome was defined as the penetration of the WHO 8vANC policy and measured as the proportion of women who used a minimum of 8vANC out of the total number of women who had live births within two years before the survey in 2021. We used multilevel modeling mixed effects logistic regression for the statistical analyses because of its ability to examine contextual effects in cross-sectional data. Results The results revealed that the residual variation in state-level 8vANC utilization––after accounting for the explanatory variables–attributable to between-state differences went from 46% in the unadjusted model to11% in the final adjusted model. The findings indicated that women in Southern states had the highest odds of 8vANC utilization. We also found that women who self-reported their perception of life satisfaction as ‘very happy’ (OR: 1.81, 95% C.I: 1.25–2.63, p = 0.002), and ‘somewhat happy’ (OR: 1.63, 95% C.I: 1.14–2.40, p = 0.012) had the highest odds of 8vANC utilization across states. Conversely, the perception of wife beating justified ‘if she goes out without telling husband’ had low odds (OR: 0.77, 95% C.I: 0.61–0.97, p = 0.032) on the penetration of the WHO 8vANC policy across states. Conclusion A greater proportion of the observed differences in 8vANC penetration occurred among women nested within states than between states. Our findings support the need for a revised policy that promotes the integration of routine prenatal mental health screening into the current ANC model. Clinical trial number Not applicable.